Gambaran Persepsi Anak tentang Kekerasan Seksual dan Pencegahannya di SDN 03 Lubuk Begalung - Lindawati; Ningsih, Elsa Agustia; Rikandi, Meta (Jurnal Kesehatan Lentera 'Aisyiyah, 2025)
Sexual violence against children is a serious violation of human rights that impacts their physical, psychological, social, and developmental well-being. Elementary school children are particularly vulnerable due to limited knowledge and lack of courage to report incidents. This study aimed to describe children’s perceptions of sexual violence and its prevention at SDN 03 Lubuk Begalung, Padang City, in 2025. The research used a descriptive design with a population of all grade IV, V, and VI students, totaling 83 children, selected through total sampling. Conducted from August 4–6, 2025, the study employed a validated and reliable questionnaire, with data analyzed univariately and presented in frequency distributions and percentages. Results showed that 57.8% of students had poor perceptions of sexual violence, while 51.8% demonstrated inadequate prevention attitudes. The conclusion indicates that most students still lack proper understanding and preventive attitudes regarding sexual violence. These findings highlight the urgent need for continuous education from schools and parents to equip children with knowledge and skills to protect themselves from sexual violence at an early age. Strengthening awareness programs and involving families in prevention efforts are essential to ensure children’s safety and resilience against such threats.